Reoviruses hijack the SMARCB1-MYC transcriptional regulation complex to activate autophagy for persistent viral infection in leafhopper vector - Wang, Hui; Liu, Runfa; Xiao, Guangming; Li, Yanan; Li, Bozhong; Chen, Qian; Wei, Taiyun (PLoS pathogens, 2025)
Autophagy plays a crucial role in virus-host interactions, as viral components and particles can be degraded by the host’s autophagic machinery. Additionally, some viruses can hijack autophagy for their own benefit. However, the mechanisms underlying the transcriptional regulation of autophagy by arboviruses in insect vectors remain largely unexplored. In this study, we found that rice dwarf virus (RDV) infection activates the autophagy pathway in the leafhopper vector, Nephotettix cincticeps , and this autophagy activation also facilitates viral infection in the leafhopper. We identified that MYC transcription factor regulates the expression of autophagy proteins ATG5 and ATG8 by directly targeting their promoters. A transcription regulator SMARCB1 binds to MYC and impedes its recognition of the ATG5 and ATG8 promoters, thus negatively regulating their expression. Moreover, NcSMARCB1 negatively regulates ATG5 expression by directly binding to its promoter. RDV major outer capsid protein P8 blocks the nuclear translocation of SMARCB1, disrupting the SMARCB1-MYC interaction and thereby relieving the transcriptional inhibition of ATG5 and ATG8, which leads to autophagy activation. Furthermore, major outer capsid protein P8 of rice gall dwarf virus (RGDV), same to RDV belonging to plant reoviruses, also interacts with SMARCB1 in leafhopper Recilia dorsalis , preventing its nuclear translocation. Similarly, suppression of SMARCB1 expression enhances autophagy formation and promotes RGDV infection. These findings highlight the critical role of insect vector SMARCB1 and MYC in regulating autophagy in response to arbovirus infection.